Avaliação do processo de implementação da estratégia "e-sus atenção básica" no município de apodi-rn: uma análise a partir do modelo do ciclo de políticas públicas (policy cycle) - Câmara Neto, Jaime Virgínio (2019)
The main objective of this study is to evaluate the efficiency of the implementation process of the "e-SUS Basic Care" Strategy in the city of Apodi-RN, using the policy cycle model. To do this, we set out some specific objectives, such as: identifying the personal characteristics and influence of the professional profile of the program participants in their implementation process; verify the operational capacity of the teams and professionals, and finally, evaluate the infrastructure of the Basic Health Units, in accordance with the requirements of the e-SUS Strategy. The research consists of a case study of descriptive character, based on the qualitative method, using the technique of content analysis. It had as social actors researched: the former coordinator of Basic Attention; the current coordinator and the 85 professionals who integrate the Family Health teams (ESF), the Oral Health teams (ESB) and the Community Health Agents (EACS) team; all belonging to the municipality of Apodi-RN. Data collection, in secondary terms, occurred through extensive bibliographical research as well as extensive documentary research, through the analysis of ordinances, technical notes and resolutions of the collegiate bodies. Already, in primary terms, the data collection took place through the application of questionnaires with the members of the program teams, and through semi-structured interviews with the former coordinator and the current managers of Basic Care. The results showed that the majority of professionals were female, aged between 40 and 50 years and with more than 15 years of primary care, revealing that adherence to the Strategy had a strong impact on the work process of these professionals. Although most of the respondents report aptitude for computer use, some still use paper chips and do not know how to handle e-SUS softwares, mainly because of deficiencies in training. The research also revealed that the UBS does not have minimum infrastructure for program implementation, especially due to the lack of computers, tablets and printers; lack of good quality internet supply and lack of computer technical support. Thus, the municipality of Apodi-RN was not able to definitively implement e-SUS, since the system with PEC, which consists of the permanent system of the program, still does not work, remaining the system with CDS, which according to with the Ministry of Health, should have closed its activities since the year 2016